Characteristics study of carbon fibre material for BioApps RoMicP® foot prosthesis / Shen Wenhui - Shen, Wenhui (2021)
In this research project, to study the characteristics of materials used in BioApps RoMicP® Foot Prothesis and improve its performance in diferrent parts which are in different positions and can withstand different types of force. The material studies is the composite including Onyx and Carbon Fiber(CF) which were utilized in markforged Mark-Two 3-D printer to produce a light foot prosthesis with high performance and low cost. To investigate the mechanical properties, samples with different CF contribution way and with different components of carbon fiber were produced. Three types of mechanical test involving tensile test, compression test and 3-point bending test were conducted. Then, through calculation and analysis of the yield strenght, yield modulus respectively to get the most excellent design of each part. In tensile test, the testing sample with 80% Onyx and 20% carbon fiber embedded in the middle behaves best, its yield strength is 117.1 MPa and yield modulus in 2.065 GPa. In compression test, the specimenwith 10% carbon fiber printed in the middle showed the best performance, its yield strength is 5.03 MPa and yield modulus is 23.0 MPa. In 3-point bending test, the results of testing sample with 20% carbon fiber distributed at the both ends is most excellent, its flexural strength is 81.68 MPa and flexural modulus is 4.464 GPa. Therefore, according to the above results, we can design and print different parts in foot prosthesis to optimiza their performance.